Bundling socio-technical innovations to empower women as partners and drivers of climate change solutions - Nchanji, Eileen; Puskur, Ranjitha; Lutomia, Cosmas Kweyu; Ketema, Dessalegn Molla; Gartaula, Hom Nath; Mukhopadhyay, Prama; Mapedza, Everisto D.; Johnstone, Kevin; Barrett, Sam (2023)
The CGIAR Initiative on Gender Equality (HER+: Harnessing Gender and Social Equality for Resilience in Agri-food systems) aims to achieve climate resilience by strengthening gender equality and social inclusion across food systems in the Global South. Together with partners, the initiative supports women to increase their agency and to acquire and gain control over resources. The initiative facilitates women’s pathways to empowerment and helps them adapt to future climate-related shocks and stresses. The initiative addresses four areas of gender inequality in the AFS: access to resources, women’s agency, social norms and policies, and governance. The work in these four areas is divided into four work packages. This workshop is part of Work Package 2. This work package aims to achieve climate resilience by strengthening gender equality and social inclusion across food systems in the Global South. We develop and test context-specific bundles of social and technological innovations with the aim increasing adoption and benefits for women in agri- food systems. As a part of this work, the IIED developed a draft framework based on the STIBs concept. The framework links access to productive technologies, resources, and services to achieving healthy, equitable, resilient, and sustainable (HERS) outcomes for farmers (Barrett, 2022). It has a strong focus on gender and empowerment. The framework was developed from a literature review of studies and reports that discussed gender, technology, resilience, climate smart agriculture, and documented outcomes. The team used a realist synthesis methodology to unpack the contexts, mechanisms for change, and the outcomes from the studies identified. The IIED team then interviewed experts who later suggested adjustments based on their experience. In the workshop, the IIED team shared the draft framework with participants who included researchers and practitioners in the agricultural research for development sector. They then sought feedback from participants to fine-tune and validate the framework. IIED also tested the application of this framework to specific projects, selecting context-specific interventions to build suitable STIBs that generate better outcomes and broader impacts. The framework will support the implementation of the learning labs in different agro-ecological and socio-cultural contexts across Africa and Asia.